비할로겐계 난연성 고분자용 탄소계 나노 첨가제의 용융 유황 응용 - 박훤; Hwon Park; 하재석; Jaeseok Ha; 남기호; Ki-ho Nam; 배진석; Jin-seok Bae (한국섬유공학회지, 2024)
The excessive accumulation of sulfur from industrial processes poses a significant environmental challenge, contributing to acid rain, air pollution, and soil contamination. While managing this surplus sulfur is challenging, it has the potential to be repurposed into sustainable materials through proper utilization. This study introduces a novel approach to sulfur management by employing elemental sulfur as a reducing agent to synthesize sulfur-doped reduced graphene oxide (S-rGO). The S-rGO was incorporated into a porous polyimide (PPI) matrix to create a high-performance composite with enhanced flame retardancy, thermal stability, and tailored porosity. Comprehensive characterization revealed that sulfur doping introduced structural defects, which contributed to the material's improved functional properties. Additionally, the porosity in the PPI/S-rGO composite, combined with varying filler contents, enhanced thermal stability, dynamic storage modulus, and flame retardancy. This work provides a sustainable solution for sulfur management and presents a multifunctional material suitable for applications in industries requiring flame-retardant, thermally stable, and porous polymers, such as semiconductor coatings and battery separators.